Can the agroprocessing sector create jobs in Africa? Evidence from Ethiopia, Ghana and Tunisia - Zaneta Kubik; Tigabu Degu Getahun; Rose Omari; Meriem Oueslati Zlaoui (University of Bonn, Center for Development Research (ZEF), 2022)
This paper analyzes the potential of the agroprocessing sector to create jobs in Africa, based on the evidence from Ethiopia, Ghana and Tunisia. The analysis uses both primary qualitative data and secondary quantitative data on formal firms and workers in the agroprocessing sector and shows how responsive the sector is to the growing consumer demand and how it translates into employment generation. Agroprocessing sectors in Ethiopia, Ghana and Tunisia differ greatly in terms of the size and structure, and, accordingly, the stages of industry lifecycle, from nascent industry in Ethiopia to a relatively mature sector in Tunisia. Also, the type of jobs and their quality differ between the three countries even though they are generally considered to be good jobs compared to other jobs available to the same workers. So far, the potential of the agroprocessing sector remains largely untapped. Formal sector employs between 60 and 80 thousand people in each of the study countries, and the figure is around five times higher if employment in the informal sector is included. As of now, employment in agroprocessing activities accounts for only around 5% of total employment in the food economy. However, over the last two decades, it has grown rapidly. In Ethiopia, Ghana and Tunisia, the agroprocessing sector exhibits high employment elasticities of output, from 0.55 in Ghana and 0.66 in Tunisia to 0.85 in Ethiopia. This suggests that the agroprocessing sector is labor-intensive and presents high employment generation potential, both in absolute terms and compared to other sectors of manufacturing. On the other hand, if agroprocessing firms shift toward more capitalintensive production structures and use more mechanization and automation, the expected employment effects remain ambiguous.
Keywords: J23; J43; J80; L66; 330; agroprocessing; food; beverages; manufacturing; employment; labor demand; inclusiveness